Influences of wind and humidity on thermal comfort in urban canyons of Bandar Abbas, Iran - Dalman, Masoud (2012)
Accessibility to thermal comfort spaces for citizens and urban outdoor activities could be one of the main goals of urban designers. Urban forms and canyons have an important role on the microclimate and thermal comfort condition in such situations. Hence there is a need to understand the dynamics of urban fabric and microclimate of an urban area for good urban design of outdoor spaces. Bandar Abbas city, located in the southern part of Iran at the northern rim of Hormuz Strait, is an example of an urban growth area with a combination of traditional and modern urban fabrics. The hot and humid climate of Bandar Abbas, especially in long summers causes thermal stress for urban activities. The aim and objectives of the present study is to investigate the possibilities that achieve thermal comfort in residential urban canyons of new developments thus improve life style for outdoor environments in Bandar Abbas. To achieve these aims,this study selected two different urban fabric typologies to identify the prevailing urban canyon patterns, to investigate microclimate conditions and explore thermal comfort situation to propose new urban design strategies for comfortable outdoor spaces. This research employs various research techniques involving quantitative and qualitative approaches and comprising a case study of Bandar Abbas through direct observation of urban fabric, field measurement of climatic elements, and computer simulation of wind flow patterns. To understand the influence of microclimate factors and thermal comfort situations in the study area, two different typologies of traditional and new residential development (modern) urban fabrics have been selected in south east of Bandar Abbas. The results indicate that the traditional urban fabric is more thermally comfortable than the new residential urban fabric. According to the field measurements, thermal comfort calculation and wind simulations, the canyons with North-South direction represents better orientation for air circulation benefiting from sea breezes as compared to other canyon orientations. The findings will throw light on the urban designers and policy makers of cities which have the same climate especially in Persian Gulf region and tropical hot and humid climate with similar conditions.